Analysis of the molecular mechanism regulating anther endothecium secondary thickening in Arabidopsis thaliana - Fairburn, Stefan (2020)
Food security is important to feed a growing global population in a changing climate. Heterosis (the phenomenon of increased yield in hybrid crops) is a significant way to maximise crop yields without increasing input. One difficulty with breeding hybrid plants is preventing self-fertilisation, and there is therefore interest in male sterile plants in commercial crop systems. This can be achieved by controlling development or release of pollen.